Effect of Massage Combined Speech Training on Phonological Disorder in Children with Dyskinetic Cerebral Palsy - Jinrong HUANG; Feng ZHANG; Fujian CHEN; Jiaoyan LIAO; Bo LI (康复学报)
Objective:To observe the effect of massage combined speech training on the phonological disorder in children with dyskinetic cerebral palsy, and search for approaches which may improve sound constructing, verbal fluency, articulation, diadochokinetic rate, speaking rate etc..Methods:Two children with dyskinetic cerebral palsy aged, six, seven years old, were recruited in this study, treated with massage combined speech training, and selected as a case study of A-B-A. Speech samples of two patiens were collected by real-time speech measuring instrument. The samples were arranged and the sound constructing, verbal fluency and articulation were analyzed.Results:After massage combined speech training, two children gained significant improvement in the indexes of sound constructing, verbal fluency, articulation, diadochokinetic rate and speaking rate.Conclusion:Massage combined speech training has a significant impact on the improvement of sound constructing, verbal fluency and articulation in children with dyskinetic cerebral palsy.